Evaluating the Environmental Impact of Ethanol Fuel: Particle Number Emissions in Flex-Fuel Vehicles (Global Journal of Human-Social Science, 2023)
In Europe the EURO 6 Light Duty emission standards a consequence of Diesel vehicles introduced limits for particle number PN of Gasoline Direct Injection GDI engines Given the extremely small particles concern about health effects the same limits were set 6 0 x 1011 km for diesel and GDI cars In Brazil the current phase for light vehicles of PROCONVE L6 enforced particulate matter PM mass emission standards for Diesel vehicles only applying the limits of 25 mg km for passenger cars and 30 mg km for commercial vehicles Similar to the European concern even not considering the particle number PN emissions future Brazilian phase L7 which is under study considers a significant reduction in the limit of the particulate matter PM mass emission from current limits down to 6 mg km for both Diesel and DI engines for passenger and commercial vehicles Aiming to contribute to hydrated ethanol fuel sustainability discussion compared to gasoline and for generating reference data regarding particle number PN emissions which can be used for future emissions regulations of Flex-Fuel vehicles in the Brazilian market this article explores particle number PN measurements of Flex-Fuel Vehicles equipped with direct injection DI and port fuel injection PFI engines fueled with ethanol E100 and gasohol E22
Keywords: ethanol; sustainability; particle number; particle matter